ГЕОМОРФОЛОГИЯ И ЛИТОЛОГИЯ ДЕЛЬТЫ ЧЖУЦЗЯН (КИТАЙ) - Коротаев В.Н.; Михайлов В.Н.; Михайлова М.В.; Ли Цзунсянь (My University, 2006)
Geomorphology and history of the development of the Zhujiang River delta during the postglacial time are described. Special attention is given to the lithologic structure of deltaic plain and distribution of recent sediments in the deltaic distributaries and at mouth seashore (delta front and prodelta). Two stages of delta formation are revealed: 1 - long period of slow development, 2 - the late 2500 years of rapid development.
Keywords: 551.4.435.126(282.252)